2014
DOI: 10.1093/hmg/ddu360
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic severity of homozygous GCK mutations causing neonatal or childhood-onset diabetes is primarily mediated through effects on protein stability

Abstract: Mutations in glucokinase (GCK) cause a spectrum of glycemic disorders. Heterozygous loss-of-function mutations cause mild fasting hyperglycemia irrespective of mutation severity due to compensation from the unaffected allele. Conversely, homozygous loss-of-function mutations cause permanent neonatal diabetes requiring lifelong insulin treatment. This study aimed to determine the relationship between in vitro mutation severity and clinical phenotype in a large international case series of patients with homozygo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 35 publications
1
47
1
Order By: Relevance
“…Homozygous inactivating mutations of GCK have been repeatedly reported to contribute to PNDM, with only two exceptions, described in 9 and 15 years old white French Canadians showing mild hyperglycemia totally superimposable to that observed in GCK‐related MODY conditions (Raimondo et al, ). We here describe a novel GCK missense mutation p.E372D that in an Italian family co‐segregates with mild impairment of glucose homeostasis not only in heterozygous patients but also in the only homozygous family member who was diagnosed as diabetic in the adult life.…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous inactivating mutations of GCK have been repeatedly reported to contribute to PNDM, with only two exceptions, described in 9 and 15 years old white French Canadians showing mild hyperglycemia totally superimposable to that observed in GCK‐related MODY conditions (Raimondo et al, ). We here describe a novel GCK missense mutation p.E372D that in an Italian family co‐segregates with mild impairment of glucose homeostasis not only in heterozygous patients but also in the only homozygous family member who was diagnosed as diabetic in the adult life.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases will require lifelong insulin therapy, although partial responsiveness to repaglinide and the sulfonylurea glibenclamide have been reported [1]. Phenotypic heterogeneity has been described across recessive mutations, including atypical features such as childhood-onset diabetes, with protein instability playing the largest role in predicted severity [35]. In the heterozygous state, GCK mutations cause stable, mildly elevated fasting blood glucose levels without diabetes-related complications (GCK-MODY, [36, 37]).…”
Section: Rarer Causes Of Congenital Diabetesmentioning
confidence: 99%
“…Several hundred GCK mutations have been identified to cause diabetes. 44,45 Enzyme kinetics studies of those mutant GCK proteins showed increased S 0.5 for glucose when the mutations were located in glucose-binding sites and increased K m for ATP for ATP-binding site mutations. Some mutations led to unstable GCK proteins, while some mutations only showed decreased K cat .…”
Section: Inactivating Mutations Of Gck and Diabetesmentioning
confidence: 99%